Feira de Santana: entre culturas, paisagens, imagens e memórias visuais urbanas - um estudo que dialoga com as décadas de 1950 a 2009 - Azevedo, Livia Dias de (2010)
Feira de Santana is established as an important medium-sized city of Bahia and Brazil. According to an alleged ideal of the modern city, changes are quick and intense, using models and urban patterns that ignore their specific locations. Thus, the urban landscape and their images and memories arising from urban change rapidly. The research is developed considering the urban landscape as a sign subject to different interpretations and readings. Within this scenario, this text aims to make a visual reading, in the cultural perspective of the urban landscape of the city of Feira de Santana, Bahia, and show, through photographs, the similarities between urban landscapes of the cities of Fair Santana and Salvador. It is understood, however, the complexity involved in the structuring of local culture, since the city was influenced by major cultural venues: the coast and the hinterland of Bahia. The time frame will be addressed in a dialogic and nonlinear, and focus will be between the years 1950 to 2009. Were used as methods of the following: literature search; approach to fieldwork, observation and records of the urban landscape and Salvadoran feirense production; field diary, interviews, and production of various maps, drawings and photographic records. It was found that the city's image is built not only by the materiality of ways, but mainly by social relationships inferred these forms and their contexts-cultural-political space-time that give them meaning.